The identity of Azara´s (1805) No. 246 Trepador remos y cola roxos (Aves: Furnariidae) - Smith, Paul (Zootaxa, 2020)
The identity of Azara’s No. 246 “Trepador remos y cola roxos” and the names Dendrocolaptes miniatus Illiger, 1820 and Dendrocopus rubricaudatus Vieillot, 1818, which are based on it, have never been convincingly elucidated, and previously proposed identifications in the literature are demonstrably incorrect. Azara shot his specimen in a Paraguayan forest and provided a detailed description and measurements of it in his Spanish text. These are sufficient to confirm the identity of the specimen and the names based on it as the Olive Spinetail, long known as Cranioleuca obsoleta (Reichenbach, 1853). Dendrocolaptes miniatus Illiger, 1820 and Dendrocopus rubricaudatus Vieillot, 1818 nevertheless have date priority over that name, but as they have not been used as valid since 1899 they are nomina oblita under Article 23.9.2 of the Code. Cranioleuca obsoleta has been in universal use for this species since Hellmayr (1925), so it qualifies as a nomen protectum under Article 23.9.2, and remains the valid name for the Olive Spinetail.